Dissemination and Implementation of Shared Decision Making Into Clinical Practice: A Research Agenda. (7th December 2016) - Kanzaria, Hemal K.; Booker‐Vaughns, Juanita; Itakura, Kaoru; Yadav, Kabir; Kane, Bryan G.; Gayer, Christopher; Lin, Grace; LeBlanc, Annie; Gibson, Robert; Chen, Esther H.; Williams, Pluscedia; Carpenter, Christopher R.
Abstract: Shared decision making (SDM) is essential to advancing patient‐centered care in emergency medicine. Despite many documented benefits of SDM, prior research has demonstrated persistently low levels of patient engagement by clinicians across many disciplines, including emergency medicine. An effective dissemination and implementation (D&I) framework could be used to alter the process of delivering care and to facilitate SDM in routine clinical emergency medicine practice. Here we outline a research and policy agenda to support the D&I strategy needed to integrate SDM into emergency care.